If it's not what You are looking for type in the equation solver your own equation and let us solve it.
40+14j=2(-4j=13)
We move all terms to the left:
40+14j-(2(-4j)=0
| -2r+3=43 | | 5+6(x-2)=4-8(x-4) | | 3x=√2 | | -3+v=-6= | | 36=9-3(x-2 | | -5=4+x= | | 2.6/1.7=n/10.2 | | 8(x+6)+6=-2 | | 2(9x-7)=8 | | 5=x-3/12 | | 1/6=2/5+y | | -7=2-9m | | 36=9-3x-2 | | 11/3+1/4=x | | 0.03x=0.01x+2.9 | | v/v+2+1/v-1=1 | | 2(3x+-3)+x=1 | | -15v-40=1+8v | | 8-2x=14-2x | | 10=2-y+1 | | 3.56x+35.6=71.2 | | 36+2x=-54-3x | | 4x+7x-16=48-5x | | 8x=-2=-9+7x | | 4x+7(x)^2=2 | | 3x−8=7x+4 | | 2(3x+-21)+x=1 | | 77=3.5x | | H(t)=-16^2+50t+30 | | 2x+7=61 | | 5t–4=-2 | | 0=7x^2-112 |